ANALISIS FAKTOR PERMODALAN, KUALITAS ASET, LIKUIDITAS, EFISIENSI OPERASIONAL DAN PROFITABILITAS PADA BANK SYARIAH DI INDONESIA - Ziadatul Fadlillah; Jadzil Baihaqi (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2021)
This study examines the effect of capital, asset quality, liquidity, and operational efficiency on profitability using a dataset of 7 Islamic commercial banks in Indonesia over the 2014-2018 period. This research uses a quantitative approach. The analysis technique uses Panel Least Square processed by Eviews 8. We find that the Islamic bank’s profitability is affected by operational efficiency. Nevertheless, the capital factor, asset quality, and liquidity have no impact on the Islamic bank’s profitability. In addition, the evidence shows that the bank’s fund has not been maximized to financing.